Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen Pada Jasa Servis Kendaraan Di PT. Graha Mulia Auto Samarinda - Taghfirul Azhima Yoga Siswa3, Rudiansyah Mardiana 2 (EKONOMIA, 2020)
This study aims to determine the effect of reliability, responsiveness, assurance, attention and physical evidence partially and simultaneously on customer satisfaction in vehicle service services at PT. Graha Mulia Auto Samarinda.The theory used in this research is service quality and customer satisfaction. this research was conducted on vehicle users in Samarinda City. The population in this study is known to be taken as many as 100 respondents. Data collection is done by distributing online questionnaires from Google forms using a Likert scale to measure indicators. The analytical tool used is multiple linear regression.The results of this study in the f test showed that service quality variables which include reliability, responsiveness, assurance, empathy, tangibles have a joint effect on customer satisfaction. the t test shows that the reliability, responsiveness, assurance, empathy variables have a significant effect on customer satisfaction while the tangibles variable does not significantly influence customer satisfaction in vehicle service at PT. Graha Mulia Auto Samarinda